A SOX3 duplication and lumbosacral spina bifida in three generations. Issue 5 (31st January 2022) - Butler, Kameryn M.; Fee, Timothy; DuPont, Barbara R.; Dean, Jane H.; Stevenson, Roger E.; Lyons, Michael J.
Abstract: Chromosomal aneuploidies, microduplications and microdeletions are the most common confirmed genetic causes of spina bifida. Microduplications of Xq27 containing the SOX3 gene have been reported in 11 cases, confirming the existence of an X‐chromosomal locus for spina bifida. A three generation kindred reported here with a SOX3 duplication has been identified in one of 17 kindreds with recurrences in the 29 years of the South Carolina Neural Tube Defect Prevention Program. Other recurrences during this time period included siblings with an APAF1 mutation, siblings with a CASP9 mutation, siblings with a microdeletion of 13q, and two sets of siblings with Meckel syndrome who did not have genetic/genomic studies performed.